Integrasi Tauhid dan Khilafah Menurut Ismail Raji al-Faruqi - Muhamad Fajar Pramono; Mohamad Latief; M. Najib Abdussalam (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2022)
Abstract Khilafah is a state system in Islam that is intended to realize human goals in his life, namely to manifest God's will on earth. This divine will can only be realized if the state system is based on tauhid. Al-Faruqi is a modern Muslim thinker who is deeply concerned with integrating tauhid into various aspects of life, including the state system known as the khilafah in Islam. The objective of this study is to expound al-Faruqi's thoughts on the integration of tauhid teachings and the khilafah concept.This work is a library research with data sources in the form of books, articles, and various other publishing materials, both printed and non-printed. The data was gathered using documentary techniques, and it was analyzed using descriptive-analytical methods. This research finds that according to al-Faruqi, the khilafah is an Islamic state political system that is integrated with a belief system in the form of tauhid. According to al-Faruqi, the integration of tauhid with the khilafah was accomplished comprehensively and completely through three consensuses: consensus of vision (ijma’ al-ru’ya), consensus of will (ijma’ al-iradah), and consensus of action (ijma’ al-‘amal). AbstrakDalam Islam, khilafah adalah sebuah sistem kenegaraan yang dimaksudkan untuk mewujudkan tujuan manusia beragama, yaitu terwujudnya kehendak Allah di bumi. Kehendak Ilahi dimaksud hanya mungkin direalisasikan jika sistem bernegara itu berbasis tauhid. Al-Faruqi merupakan seorang ilmuwan muslim kontemporer yang memiliki konsern tinggi terhadap upaya integrasi tauhid dengan berbagai dimensi kehidupan, termasuk dengan  sistem bernegara yang dalam Islam disebut khilafah. Tulisan ini bertujuan mengkaji pemikiran al-Faruqi tentang  integrasi antara ajaran tauhid dan gagasan khilafah. Kajian ini merupakan penelitian kepustakaan dengan sumber data bahan-bahan pustaka berupa buku, artikel, dan berbagai materi penerbitan lainnya baik tercetak maupun non cetak. Data itu dikumpulkan menggunakan teknik dokumenter dan data yang terkumpul dianalisis memakai metode deskriptif analitis. Kajian ini menemukan bahwa menurut al-Faruqi, khilafah adalah sebuah sistem politik bernegara dalam Islam yang terintegrasikan dengan sistem keyakinan berupa tauhid. Dalam pemikiran al-Faruqi integrasi tauhid dengan khilafah itu dilakukan secara komprehensif dan total melalui tiga konsensus, yaitu konsensus visi (ijma’ al-ru’ya), konsensus kehendak (ijma’ al-iradah), dan konsensus aksi (ijma’ al-‘amal).